2021
DOI: 10.1071/sr20305
|View full text |Cite
|
Sign up to set email alerts
|

Structural and hydraulic responses of humid tropical soils to lime and organic residue amendments

Abstract: In humid tropical environments, where soils are characteristically acidic and low in organic matter, lime and organic residues have been used to improve soil quality. A systematic consideration of their interaction is, therefore, crucial for land-based ecosystem management. A 28-day incubation pot study was carried out to investigate the main and interactive effects of lime and organic residue type (corn stover and vermicompost) on aggregate stability under rapid wetting (WSAr), saturated hydraulic conductivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Soil texture is one of, if not the most important, soil parameters used by the World Reference Base as the international standard for soil classification. Soil texture determines the water‐holding capacity, porosity, and water flow dynamics of soils and is intrinsically linked to the distribution of chemical soil properties such as ECa (De Caires et al., 2023), pH (R. Francis et al., 2021), ECe (De Caires et al., 2015), macro, and micronutrients (Atwell et al., 2023), as well as aggregate stability (J. R. Francis et al., 2023; Wuddivira et al., 2013), slope stability, and suction (Roopnarine et al., 2014). Clustering analysis on bibliometric data revealed that although there has been a significant advancement in PSD measurements with remote and proximal sensing techniques being employed, sedimentation methods using hydrometer and pipette techniques are still overwhelmingly the methods of choice (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Soil texture is one of, if not the most important, soil parameters used by the World Reference Base as the international standard for soil classification. Soil texture determines the water‐holding capacity, porosity, and water flow dynamics of soils and is intrinsically linked to the distribution of chemical soil properties such as ECa (De Caires et al., 2023), pH (R. Francis et al., 2021), ECe (De Caires et al., 2015), macro, and micronutrients (Atwell et al., 2023), as well as aggregate stability (J. R. Francis et al., 2023; Wuddivira et al., 2013), slope stability, and suction (Roopnarine et al., 2014). Clustering analysis on bibliometric data revealed that although there has been a significant advancement in PSD measurements with remote and proximal sensing techniques being employed, sedimentation methods using hydrometer and pipette techniques are still overwhelmingly the methods of choice (Figure 2).…”
Section: Discussionmentioning
confidence: 99%